2019
DOI: 10.3847/1538-4357/ab4c34
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Outflow-induced Soft Lags of Galactic Black Holes

Abstract: The nature of lag variation of Galactic black holes remains enigmatic mostly because of nonlinear and nonlocal physical mechanisms which contribute to the lag of the photons coming from the region close to the central black holes. One of the widely accepted major sources of the hard lag is the inverse Comptonization mechanism. However, exact reason or reasons for soft lags is yet to be identified. In this paper, we report a possible correlation between radio intensities of several outbursting Galactic black ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…We argue that the origin of soft lag could be explained by the downscattering of the hard radiation in the ROF region. Similar correlations for other sources at high inclination angle were found and reported [36].…”
Section: Discussionsupporting
confidence: 90%
“…We argue that the origin of soft lag could be explained by the downscattering of the hard radiation in the ROF region. Similar correlations for other sources at high inclination angle were found and reported [36].…”
Section: Discussionsupporting
confidence: 90%
“…Also, (Dutta & Chakrabarti 2016;Chatterjee et al 2017b) reported in a different context that the X-ray lag has a strong dependency on the geometric structure of the Comptonization region and orientation of the Keplerian disc. The net delay is a resultant effect of different physical mechanisms, e.g., Comptonization, reflection, focusing, and jet/outflow emission (Chatterjee et al 2019;Patra et al 2019). For the lower inclination and radio-quiet nature of Ark 120, the positive delay could be attributed to the Compton delay while reflection and light-crossing delay could contribute to the negative delay.…”
Section: Discussionmentioning
confidence: 99%
“…The degeneracy in the inclination angle, originated mostly from spectral fitting, suggests an exploration of all possible origins of broad iron lines; (a) enhanced reflection caused by gravitational bending (Fabian & Vaughan 2003), (b) jet Comptonization mechanism (Laurent & Titarchuk 2007). It was also observed that the disk-jet coupling affects the timing properties (Gandhi et al 2008;Altamirano & Méndez 2015;Veledina et al 2017;Reig et al 2018;Patra et al 2019) as well as the spectral properties (Merloni et al 2003;Corbel et al 2003). In the case of XTE J1650-500, Curran et al (2012) reported that the jet reprocessed the X-rays emitted from the Compton cloud and the contribution of jet reprocessing can be seen in the optical-NIR flux during the rising phase.…”
Section: Xte J1650-500mentioning
confidence: 99%
“…Recently, a suggestion was made that the soft lags (Chatterjee et al 2019) of XTE J1550-564 during its outburst in 1998 could be jet induced. Following that, Patra et al (2019) inspected four high inclination GBHs where the presence of soft lags are seen during higher activity in radio fluxes. During the rising phase of XTE J1650-500, Corbel et al (2004) reported radio activity and Curran et al (2012) analyzed optical-NIR wavelengths where pieces of evidence of X-ray photons reprocessed within the jet medium were observed.…”
Section: Disk-jet Connection In Xte J1650-500mentioning
confidence: 99%